Morphometric Analysis of Celiac Trunk in Male and Female Adults of Karachi by using 3D Multidetector Computed Tomography Angiography (MDCTA) - Rosheena Nabeel Khan; Nuzhat Hassan; Madeeha Sadiq; Muhammad Ali (Journal of Bahria University Medical and Dental College)
Objective: To determine the length and diameter of celiac trunk by using Multidetector computed Tomography Angiography (MDCTA) and to find its association with gender. Methodology: 160 individuals, 85 (53.1%) males and 75 (46.9 %) females) without any vascular or upper abdominal visceral disease who presented to Radiology Department, Ziauddin University Hospital, Clifton, Karachi, for abdominal 3D MDCTA from March, 2017 to August, 2017 were recruited in this study. Length and diameter of both classical and non-classical celiac trunk was measured. Statistical analysis was done on SPSS version 20. All variables were presented as mean and standard deviation. Independent T test was applied. Correlation analysis by using Pearsons correlation was applied to test the relationship between variables. P-value 0.05 was considered significant. Result: The difference between mean length of classical celiac trunk and non- classical celiac trunk was significant (P = 0.005).The difference in mean length (P = 0.007), and mean diameter (P = 0.007) of classical celiac trunk between males and females was significant. A weak positive association (r = 0.247) was found between length and diameter of classical celiac trunk (P = 0.004). A moderate positive association (r = 0.401) was found between length and diameter of non-classical celiac trunk (P = 0.043).